الإكثار الخضري (بالعقل الساقية) لبعض أصناف الرمان. - الراعي جنان (Latakia University Journal -Biological Sciences Series, 2016)
تعد طريقة الإكثار الخضري بالعقل الساقية من أهم طرق إكثار الرمان، وأكثرها انتشاراً ونجاحاً في مناطق زراعته للحصول على غراس متجانسة مشابهة للنبات الأم. في هذا البحث تمّ استخدام ثلاثة أصناف من الرمان البلدي،والفرنسي، والدركوشي؛ إذْ تم أخذ العقل من أشجار سليمة خالية من الإصابات ا لحشرية والفطرية والبكتيرية . قسمت العقل إلى مجموعات، شملت خمس معاملات، ودرس أثر( الهرمون-والتنضيد- والحفظ-وعمر العقل –وطول العقل) في التجذير، وتبين أنه يمكن إكثار عقل الأصناف السابقة بسهولة دون معاملتها بالهرمون، وكانت أفضل العقل هي العقل بعمر سنة واحدة؛ إذْ كانت نسبة تجذيرها أكبر من نسبة تجذير عقل بعمر سنتين، كذلك كان أفضل طول للعقل هو (30 cm)؛ إذْ يتحقق عنده أعلى نسبة تجذير وأقوى نمو . لوحظ أنه يجب تنضيد عقل الصنف البلدي قبل زراعته، لأن التنضيد يزيد من نسبة التجذير، أما الصنف دركوشي فهو صنف سهل التجذير؛ إذْ يجذّر ّبنسبة عالية إذا تمّ تنضيده أو حفظه بظروف الظّل والترطيب الدائم قبل زراعته . The method of vegetative propagation by hard wood cutting is considered of the most important ones of prevalent and successful in its cultivation to obtain a Punica Granatum seeding which are genetically uniform. In this research,it was used three categories fPunica Granatum ,Municipal,French,Darcoche,where they were taken the hard wood cutting of sound trees which free of insecticides and fungal infections and bacteria, and divided into groups which in cluded five deals to know the effect of hormone,stratification,impact,the hard wood cutting age and its length on rooting. It was found that the last three tested categories had no hormone effects on rooting. The soft wood cutting of one year-old overtook the ones of two-years of age,where they have the largest effect of rooting.The highest precentage of rooting and stronger were at the length of 30 cm. Its advised for stratification of the Municipal class befor its cultivation because it increases the rooting percentage. Darcoche is easy for rooting, because it roots by ahigh percentage if it had a stratification or impact by the conditions of continuous wetting before cultivation.